2017
DOI: 10.1002/2017ja024216
|View full text |Cite
|
Sign up to set email alerts
|

Imprints of Quasi‐Adiabatic Ion Dynamics on the Current Sheet Structures Observed in the Martian Magnetotail by MAVEN

Abstract: Numerous studies of the current sheets (CS) in the Earth's magnetotail showed that quasi‐adiabatic ion dynamics plays an important role in the formation of complicated multilayered current structures. In order to check whether the similar mechanisms operate in the Martian magnetotail, we analyzed 80 CS crossings using MAVEN measurements on the nightside of Mars at radial distances ~1.0–2.8RM. We found that CS structures experience similar dependence on the value of the normal component of the magnetic field at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 78 publications
(137 reference statements)
1
23
0
Order By: Relevance
“…Similar conditions can occur in the Martian magnetotail. Recently, Grigorenko et al (2017) showed that observed heavy ion (O + and O 2 + ) population can results in the current sheet broadening due to the formation of "oxygen current wings" at the edges of a thin current layer. This phenomenon in the Earth and Martian magnetotail current sheets has been explained by the universal principles of nature.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…Similar conditions can occur in the Martian magnetotail. Recently, Grigorenko et al (2017) showed that observed heavy ion (O + and O 2 + ) population can results in the current sheet broadening due to the formation of "oxygen current wings" at the edges of a thin current layer. This phenomenon in the Earth and Martian magnetotail current sheets has been explained by the universal principles of nature.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…In our previous studies of the Martian CSs (Grigorenko, Shuvalov, Malova, Dubinin, et al, ,Grigorenko, Shuvalov, Malova, Popov, et al, ) we used the smoothed full‐resolution magnetic field data by the 4‐s sliding average to reconstruct the spatial profiles of B L ( l N ) and J M ( l N ). This allowed us to resolve the embedding current structures at ion scales (Grigorenko, Shuvalov, Malova, Dubinin, et al, ). Now we use two intervals for the magnetic field smoothing: the 1‐s sliding average to resolve a STCS near the neutral plane within| l N |≤ 20 km, and 4‐s sliding average for the analysis of the current structure at ion scales ( l N > 20 km).…”
Section: Maven Observation Of Sub‐ion Scale Stcsmentioning
confidence: 99%
“…For the statistical study of the STCSs characteristics we used a list of the 80 CS events published by Grigorenko, Shuvalov, Malova, Dubinin, et al (). The CS observations were made by MAVEN spacecraft at −2.8 R M ≤ X MSO ≤ − 1.0 R M and −1.0 R M ≤ Y MSO ≤ 1.0 R M .…”
Section: Statistical Study Of Stcss Characteristics In the Martian Mamentioning
confidence: 99%
See 2 more Smart Citations